2016
DOI: 10.21859/jne-05046
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family-Centered Empowerment Model on the Knowledge, Attitudes and Self-efficacy of Mothers of Children with Asthma

Abstract: Introduction: The purpose of this study was the assessment of family-centered empowerment program on knowledge, attitudes and self-efficacy of mothers of children with asthma. Methods: This clinical trial study was performed during year 2012. In this study, 172 mothers of children aged 6 to 12 years with asthma, who had the inclusion criteria were selected from an available sample. The samples were selected and divided to two groups of case and control. This study was conducted in three phases: pre-interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
1
9
0
1
Order By: Relevance
“…This nding is in line with the results of some studies [15][16][17][18]. Also, studies aimed at investigating the effect of family-centered education on increasing parental awareness and self-e cacy in weight control and physical activity and caring for a child with asthma and epilepsy, showed that education can increase self-e cacy and improve home care effectively [19][20][21][22]. Self-e cacy is a principle that links knowledge and behavior.…”
Section: Discussionsupporting
confidence: 88%
“…This nding is in line with the results of some studies [15][16][17][18]. Also, studies aimed at investigating the effect of family-centered education on increasing parental awareness and self-e cacy in weight control and physical activity and caring for a child with asthma and epilepsy, showed that education can increase self-e cacy and improve home care effectively [19][20][21][22]. Self-e cacy is a principle that links knowledge and behavior.…”
Section: Discussionsupporting
confidence: 88%
“…Around 5% of the total global population (around 300 million) and 7% of the total population of the United States (22.2 million people) suffer from asthma (2). The prevalence of asthma among the total population of Iran and among Iranian children is 5.5% and 10%, respectively (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…There is no definitive treatment for asthma. Yet, most patients with asthma can effectively manage the disease and its complications through adhering to their treatment and dietary regimens, taking anti-inflammatory medications, and avoiding allergens (3). Moreover, educational programs for parents can help them prevent or minimize asthma complications.…”
Section: Introductionmentioning
confidence: 99%
“…11 Highlighting the participation of families in empowerment groups and their contributions to the care of children with CKD, 35 an activity that can increase the quality of life of children with CKD, 24 because the application of the family-centered empowerment model influences knowledge, attitudes and parents' self-efficacy in controlling and managing their child's disease. 34 When carefully analyzing the different approaches described in the studies, it is highlighted that the care for the family of the child with CKD, which implies major changes in family life, as its structure undergoes exhausting adaptations to face the disease 14 and this transition can provide the transformation in the care. 35 The analyzed studies allowed to evidence different ways to evaluate and or intervene with the family of the child and/or adolescent, considering that there is no single model of approach to the family.…”
Section: Implications Of Family Intervention Strategiesmentioning
confidence: 99%